2012
DOI: 10.1159/000343330
|View full text |Cite
|
Sign up to set email alerts
|

SGK3 Regulates Ca2+Entry and Migration of Dendritic Cells

Abstract: Background/Aims: Dendritic cells (DCs) are antigen-presenting cells linking innate and adaptive immunity. DC maturation and migration are governed by alterations of cytosolic Ca2+ concentrations ([Ca2+]i). Ca2+ entry is in part accomplished by store-operated Ca2+ (SOC) channels consisting of the membrane pore-forming subunit Orai and the ER Ca2+ sensing subunit STIM. Moreover, DC functions are under powerful regulation of the phosphatidylinosito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…Here we showed that SERCA2b is required for ERα expression, and SGK3 preserves SERCA2b function in AIresistant cells, although the detailed mechanism still needs to be resolved. Recently, Schmid et al reported that SGK3 regulates Ca 2+ entry in dendritic cells through up-regulation of STIM2 expression (44). Our study suggests SGK3 maintains EnR Ca 2+ homeostasis through preserving SERCA2b function, and thus protects against excessive EnR stress, which results in ERα depletion and cell death in AI-resistant cells.…”
Section: Sgk3 Retains Erα Expression By Protecting Against Enr Stress-supporting
confidence: 52%
“…Here we showed that SERCA2b is required for ERα expression, and SGK3 preserves SERCA2b function in AIresistant cells, although the detailed mechanism still needs to be resolved. Recently, Schmid et al reported that SGK3 regulates Ca 2+ entry in dendritic cells through up-regulation of STIM2 expression (44). Our study suggests SGK3 maintains EnR Ca 2+ homeostasis through preserving SERCA2b function, and thus protects against excessive EnR stress, which results in ERα depletion and cell death in AI-resistant cells.…”
Section: Sgk3 Retains Erα Expression By Protecting Against Enr Stress-supporting
confidence: 52%
“…Ouabain-sensitive K ϩ -induced currents (Ipump) reflecting Na ϩ /K ϩ -ATPase activity were determined by whole cell patch-clamp recording in human Jurkat T cells before and following energy depletion with 2 mM DNP for 4 h in the presence and absence of JAK2 inhibitor AG490 (40 M) (preincubation 1 h before addition of DNP). Alternatively, Jurkat cells were pretreated with AG490 (40 M) alone for 4 h. Patch-clamp experiments were performed at room temperature in voltage-clamp, fast whole cell mode (35,70,79). Cells were continuously superfused through a flow system inserted into the dish.…”
Section: Methodsmentioning
confidence: 99%
“…Orai and NCX dependent Ca 2+ oscillations are further instrumental in the stimulation of cell migration [52][53][54]. Accordingly, Orai1, 2, or 3 [6][7][8][9], their regulators STIM 1 or 2 [12,13,15] and Na + /Ca 2+ exchangers [55] are involved in the regulation of survival, proliferation, and migration of tumor cells [56][57][58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%